ANALISA KEBIJAKAN RESPONSIF GENDER DI LINGKUNGAN PERGURUAN TINGGI (STUDI KASUS DOSEN DAN TENAGA KEPENDIDIKAN UPN VETERAN JAWA TIMUR) - Januari Pratama Nurratri Trisnaningtyas; Firsty Chintya Laksmi Perbawani (Halu Oleo University, 2023)
The purpose of this writing is to analyze and determine Gender Responsive Policy Analysis In The Higher Education Environment (Case Study Of Upn Veteran East Java Lecturer And Educational Personnel). The research method uses a mixed methods research approach with questionnaire data collection techniques and focus group discussions (FGD). The research results show that although the policies within the UPN